La evasión tributaria en el ecuador enfocada al impuesto al valor agregado (iva) en el comercio informal. - Castro Pazmiño, Gabriela (2015)
The Constitution of the Republic of Ecuador defines to the tributary regime in the following terms: “The tributary regime will be in force by the principles of majority, progressiveness, efficiency, administrative simplicity, non retroactive character, fairness, transparency and tax collecting sufficiency. The direct and progressive taxes will be prioritized. The tributary policy will promote the redistribution and will stimulate the use, the ecological, social production of goods and services, and conducts and economic people in charge”. For the exercise of its functions, the State requires of the economic means that allow their accomplishment him, all this implies the great number of resources that the State requires to cover its needs. The development of the present investigation leaves from the study of the financial right and its classification in tributary fiscal and right. On the other hand, the financial right is a branch of the public Right that takes care to order the income and the expenses public, normally anticipated in the general Budget of the State. The financial activity of the State generates a set of legal relations between the different organs public. This financial activity of the State generates legal relations between the State and the individuals, and it occurs in two situations: first in which the State assumes an active role, for example when receiving tributes, and a passive paper when one becomes indebted in case of a loan. In the development of the investigation process an analysis took place in detail of the historical aspects, conceptual, general norms and all the elements that sustain the financial and tributary activity of the State. The fundamental principles of the tributary regime, the importance and all the elements that turn on the tributary obligation, the generating fact and the fiscal evasion derived from the practice of the informal commerce. Finally the analysis referring to the evasion of taxes on the part of the informal commerce, and the necessity stands out to incorporate legal reforms typifying like east disobedience type of commercial practice. In our country they exist trading national and foreign unreliable people who on a large scale realize their mercantile activities without telling on the respective affiliation a Chamber of Commerce, matriculation, nor count on the unique registry of contributor (RUC), reason why easily evade tributes that by law are forced to declare: IVA, ICE. The tributary evasion directly affects the capacity of state financing, causing that the standard of life of its inhabitants falls progressively.